Solid particle erosion of plasma sprayed ceramic coatings - Branco,José Roberto Tavares (2004)
Thermal spraying allows the production of overlay protective coatings of a great variety of materials, almost without limitations as to its components, phases and constituents on a range of substrates. Wear and corrosion resistant coatings account for significant utilization of thermal spray processes. Besides being a means to evaluate the coating tribological performance, erosion testing allows also an assessment of the coating toughness and adhesion. Nevertheless, the relationship between the erosion behavior of thermal sprayed coatings and its microstructural features is not satisfactorily understood yet. This paper examines room temperature solid particle erosion of zirconia and alumina-based ceramic coatings, with different levels of porosity and varying microstrucutre and mechanical properties. The erosion tests were carried out by a stream of alumina particles with an average size of 50 µm at 70 m/s, carried by an air jet with impingement angle 90°. The results indicate that current erosion models based on hardness alone cannot account for experimental results, and, that there is a strong relationship between the erosion rate and the porosity.